2008
DOI: 10.1029/2007gl032583
|View full text |Cite
|
Sign up to set email alerts
|

CO2 sensitivity of Southern Ocean phytoplankton

Abstract: The Southern Ocean exerts a strong impact on marine biogeochemical cycles and global air‐sea CO2 fluxes. Over the coming century, large increases in surface ocean CO2 levels, combined with increased upper water column temperatures and stratification, are expected to diminish Southern Ocean CO2 uptake. These effects could be significantly modulated by concomitant CO2‐dependent changes in the region's biological carbon pump. Here we show that CO2 concentrations affect the physiology, growth and species compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
266
9
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 273 publications
(316 citation statements)
references
References 24 publications
32
266
9
3
Order By: Relevance
“…Both diatoms and coccolithophores were the only other phytoplankton groups to show a constant increase in biomass in the control treatment which was greater than that of the high CO 2 treatment, but only significant for coccolithophores. The overall increase in total community biomass followed the same trend as previous studies conducted on natural phytoplankton community CO 2 enrichments (Feng et al, 2009;Hare et al, 2007b;Riebesell et al, 2007;Tortell et al, 2008). The only groups/ species to show an overall net gain in biomass in the high CO 2 treatment, irrespective of significant increases (or decreases) relative to the control community following target pCO 2 equilibration were diatoms, Phaeocystis spp.…”
Section: Elevated Pco 2 Perturbation Experimentssupporting
confidence: 82%
See 1 more Smart Citation
“…Both diatoms and coccolithophores were the only other phytoplankton groups to show a constant increase in biomass in the control treatment which was greater than that of the high CO 2 treatment, but only significant for coccolithophores. The overall increase in total community biomass followed the same trend as previous studies conducted on natural phytoplankton community CO 2 enrichments (Feng et al, 2009;Hare et al, 2007b;Riebesell et al, 2007;Tortell et al, 2008). The only groups/ species to show an overall net gain in biomass in the high CO 2 treatment, irrespective of significant increases (or decreases) relative to the control community following target pCO 2 equilibration were diatoms, Phaeocystis spp.…”
Section: Elevated Pco 2 Perturbation Experimentssupporting
confidence: 82%
“…Similarly in some natural phytoplankton communities exposed to elevated pCO 2 (750 ppmv) diatoms and prymnesiophytes become dominant, making up 60% and 30% of the total biomass (Tortell et al, 2002). Tortell et al (2008) also observed in Ross Sea phytoplankton, a shift in dominance from Phaeocystis antarctica (contributing > 90% community biomass) to large chain-forming diatoms (Chaetoceros spp.) within high CO 2 treatments (800 ppmv).…”
Section: Elevated Pco 2 Perturbation Experimentsmentioning
confidence: 80%
“…Responses of marine microbes to elevated pCO 2 differ among studies. A number of studies conducted in polar waters indicate that moderate enhancement of CO 2 concentration promotes phytoplankton production and fosters the growth of large diatoms (Engel et al, 2008;Tortell et al, 2008a;Feng et al, 2010), while others find it promotes the growth of pico-and nanoplankton (Hare et al, 2007;Brussaard et al, 2013). Overall, differences in competitive fitness among phytoplankton functional groups indicate that exposure to elevated pCO 2 could alter the phytoplankton community in coming decades (Dutkiewicz et al, 2015).…”
Section: Climate-driven Changes To the Southern Oceanmentioning
confidence: 99%
“…decreased uptake rates of CO 2 and HCO 3 − as well as lowered external CA activities (see Reinfelder, 2011). Natural phytoplankton communities of the SO (Weddell Sea, Drake Passage, Western Antarctic Peninsula, Amundsen and Ross Sea) were found to actively take up CO 2 and HCO 3 − (Cassar et al, 2004;Tortell et al, 2008aTortell et al, , 2008bTortell et al, , 2010Neven et al, 2011;Tortell et al, 2013;Kranz et al, 2015;Trimborn et al, 2015), thus indicating the presence of a CCM. Also, laboratory studies have demonstrated the operation of CCMs in various SO diatoms (Chaetoceros debilis, Fragilariopsis kerguelensis, F. cylindrus, Nitzschia frigida, Pseudo-nitzschia subcurvata) and a prymnesiophyte (Phaeocystis antarctica), although important differences between species were seen in the ratios of HCO 3 − and CO 2 uptake and external CA activity (Mitchell and Beardall, 1996;Trimborn et al, 2013;Kranz et al, 2015;Young et al, 2015).…”
Section: Ocean Acidification -Ph and Comentioning
confidence: 99%
See 1 more Smart Citation